Evaluation of nauclea diderrichii (De Wild.) merrill leaf extracts and fractions against some clinical bacterial isolates from urinary tract infections (2019)
Urinary tract infections (UTIs) constitute considerable health and economic burdens globally. The advent of resistant strains of uropathogens coupled with high rate of recurrent UTIs has heightened the precarious situation. Consequently, research efforts are being directed towards alternative treatment solutions. This study investigated the potential of Nauclea diderrichii leaf extracts and fractions as antibacterial agents against some clinical uropathogen isolates. Chloroform, acetone and methanol extracts of dried leaf of N. diderrichii, obtained by cold maceration, were evaluated for antibacterial activity against five different species (2 strains each) of clinical uropathogenic bacterial isolates from UTI; namely: Proteus mirabilis, Escherichia coli, Klebsiella pneumoniae, Enterobacter feacalis and Pseudomonas aeruginosa. The secondary metabolites present in these extracts were investigated by qualitative phytochemical screening. The most active extract was subjected to chromatographic fractionation, while the minimum inhibitory concentrations (MICs) of the fractions were determined. Chloroform extract exhibited activity against all the strains with inhibition zone diameters of 10 mm - 19 mm, while methanol and acetone extracts showed some activity against some of the organisms with inhibition zone diameters of 10 mm - 18 mm and 12 mm - 16 mm, respectively. Phytochemical screening revealed the presence of saponins, alkaloids, anthraquinones, terpenoids, cardiac glycosides, phenolics and flavonoids. Fractionation of the chloroform extract yielded three fractions, with MICs: 0.78125 - 25 mg/mL, fraction C; 1.5625 - 12.5 mg/mL, fraction B; and 1.5625 - 25 mg/mL, fraction A. This study confirmed that N. diderrichii leaf contains bioactive compounds against UTI-causing uropathogens.